2014
DOI: 10.4236/ojpsych.2014.41009
|View full text |Cite
|
Sign up to set email alerts
|

Drug use, consequences and perceived accessibility in three Nigerian universities

Abstract: Background: Use of alcohol and other psychoactive substances constitutes major public health concern, especially among adolescents and young adults. The aims of this study were to determine the prevalence and perceived accessibility of psychoactive substances. Method: This cross sectional study was conducted in three Nigerian universities with the use of United Nations Office on Drugs and Crime (UNODC) student model questionnaire. Results: Five hundred and forty-nine students participated. Majority of them wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
5
7
0
Order By: Relevance
“…Non-inclusion of tobacco and alcohol among the drugs surveyed may be responsible for this result. Furthermore, our study revealed alcohol as the second most common drug used by students consistent with the result of a previous Nigerian study (10). In contrast, it ranked first in an Ethiopian study (19), and third in a Sudanese study (16).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Non-inclusion of tobacco and alcohol among the drugs surveyed may be responsible for this result. Furthermore, our study revealed alcohol as the second most common drug used by students consistent with the result of a previous Nigerian study (10). In contrast, it ranked first in an Ethiopian study (19), and third in a Sudanese study (16).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, effective measures are required to tackle the menace of the use of these two drugs in Nigerian schools in order to enhance academic performance. Among the illicit drugs, cannabis had the highest past 12-month prevalence congruent with the finding of a previous university and population based-studies, respectively (10,16,21). Cannabis has continued to feature in Nigeria and some other countries as the most commonly used illicit drug (22).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Substance use initiation age was also signi cant in this current study where out of 3 students, 2 had used a substance before age of 18 years, which is consistent with other studies [2], [22]. The development of cognitive, emotional, and social abilities in children and adolescents get affected by substance use may compromise later functioning in important adult domains such as marriage, parenting, and gainful employment [22].…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of life time cocaine use among student was 5,7%, this rate remain higher than the ndings of university students in Nigeria where it was 2,1% [22], and also among US students where it was 4,8% [5].…”
Section: Discussionmentioning
confidence: 60%